Women's view on shared decision making and autonomy in childbirth: cohort study of Belgian women - Elke Deherder; Ilse Delbaere; Adriana Macedo; Marianne J. Nieuwenhuijze; Sven Van Laere; Katrien Beeckman (BMC, 2022)
Abstract Background Health care providers have an important role to share evidence based information and empower patients to make informed choices. Previous studies indicate that shared decision making in pregnancy and childbirth may have an important impact on a woman's birth experience. In Flemish social media, a large number of women expressed their concern about their birth experience, where they felt loss of control and limited possibilities to make their own choices. The aim of this study is to explore autonomy and shared decision making in the Flemish population. Methods This is a cross-sectional, non-interventional study to explore the birth experience of Flemish women. A self-assembled questionnaire was used to collect data, including the Pregnancy and Childbirth Questionnaire (PCQ), the Labor Agentry Scale (LAS), the Mothers Autonomy Decision Making Scale (MADM), the 9-item Shared Decision Making Questionnaire (SDM-Q9) and four questions on preparation for childbirth. Women who gave birth two to 12 months ago were recruited by means of social media in the Flemish area (Northern part of Belgium). Linear mixed-effect modelling with backwards variable selection was applied to examine relations with autonomy in decision making. Results In total, 1029 mothers participated in this study of which 617 filled out the survey completely. In general, mothers experienced moderate autonomy in decision-making, both with an obstetrician and with a midwife with an average on the MADM score of respectively 18.5 (± 7.2) and 29.4 (±10.4) out of 42. The linear mixed-effects model showed a relationship between autonomy in decision-making (MADM) for the type of healthcare provider (p < 0.001), the level of self-control during labour and birth (LAS) (p = 0.003), the level of perceived quality of care (PCQ) (p < 0.001), having epidural analgesia during childbirth (p = 0.026) and feeling to have received sufficient information about the normal course of childbirth (p < 0.001). Conclusions Childbearing women in Flanders experience moderate levels of autonomy in decision- making with their health care providers, where lower autonomy was observed for obstetricians compared to midwives. Future research should focus more on why differences occur between obstetrics and midwives in terms of autonomy and shared decision-making as perceived by the mother.